DETERMINANT FACTORS STOCK PRICE ON SHARIA SHARE PRICE AT COVID-19 PANDEMIC ERA - Lukiawati, Windi; Badina, Tenny; Fatoni, Ahmad (Management Science Research Journal, 2023)
This study aims to explain the effect of determinant factors of stock price are Earning Per Share, Current Ratio, Inflation, and Exchange Rates, whether there were differences in Stock Prices before and during the Covid-19 Pandemic era. The population of this study is Healthcare sector companies listed on the Indonesian Sharia Stock Index (ISSI) for the period 2018 – 2021. The data used in this research is panel data from 14 selected sample companies, with a total sample of 22 companies. The results of the study show that the determinant factors of stock price are earning per share has a significant positive effect on stock prices; while Current Ratio, Inflation, and Rupiah Exchange Rates have no significant effect on Share Prices; and then, there are differences in Stock Prices before and during the Covid-19 Pandemic